Therapeutic possibilities and dermatological case studies in the municipality of Mitrovica, for the winter period from 01. 11. 2021 - 31. 01. 2022 and the spring/summer period from 01. 05. 2021 - 31. 07. 2022 - Musa, Mexhit (Technium BioChemMed, 2022)
Skin diseases are most often caused by microorganisms - bacteria, viruses and fungi. In these cases, the cure is certain and the therapy is based on antibiotics, antifungals or minor interventions. Another group of skin diseases are indicators of an excessive immune response of the body to various influences. Most often we encounter different types of eczema and urticaria. The treatment of such diseases is complex, based on antihistamines and corticosteroids. Tests and analyzes are always carried out to determine the existence of a focal point in the body that leads to the appearance of the skin manifestation of a certain disease. In my research related to two institutions, and in two age periods, I came to the following data: In the Family Medical Center-Dermatology Department in Mitrovica, for the period from November 1, 2021 to January 31, 2022, requested help 714 patients and in the spring/summer period from May 1, 2022 to July 31, 2022, 1,196 patients, suffering from skin eczema, hand and foot eczema, psoriasis, seborrheic dermatitis, acne vulgaris, fungal diseases, requested help. skin, Fibromas and papilloma’s, Keratoses, Condylomas, Rosacea, facial redness, etc. Of the total number of patients, 36.90% were men, and 63.10% were women. A significant difference was recorded in the number of people suffering from Eczema compared to Psoriasis vulgaris, Acne vulgaris, Erysipelas and Melanoma (p = < 0.001). The highest consumption of medicines was for the treatment of patients with eczema (49.00%), for the treatment of psoriasis vulgaris (28.00%), acne vulgaris (11.00%), erysipelas (4.00%) and (7%) other (of the total consumption of medicines, it shows and a significant difference (p = < 0.001).A significant difference was recorded between the two periods 01.11.2021 - 31.02.2022 and from 01. 05. 2022 - 31.08.2022.